1992
DOI: 10.1007/bf00867590
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic ataxia

Abstract: Seventeen patients with hemiataxia as a manifestation of thalamic infarction were studied. Hemiataxia had the main clinical characteristics of a "cerebellar type" of ataxia, though it never occurred in isolation, being associated with ipsilateral sensory disturbance (hemiataxia-hypaesthesia) in 7 patients, with ipsilateral sensory disturbance and hemiparesis (hypaesthetic ataxic hemiparesis) in 8 patients, and with hemiparesis (ataxic hemiparesis) in 2 patients. Recovery was good, and in all patients the senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Hyperesthetic ataxic hemiparesis was described in 8 cases, hyperesthetic hemiataxia was described in 24 cases, ataxic hemiparesis was described in 11 cases and sensory hemiataxia was described in 5 cases [14, 42, 46, 47, 50, 51, 54, 55, 58, 88, 102]. Isolated hemiataxia was described in 3 cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperesthetic ataxic hemiparesis was described in 8 cases, hyperesthetic hemiataxia was described in 24 cases, ataxic hemiparesis was described in 11 cases and sensory hemiataxia was described in 5 cases [14, 42, 46, 47, 50, 51, 54, 55, 58, 88, 102]. Isolated hemiataxia was described in 3 cases.…”
Section: Resultsmentioning
confidence: 99%
“…This is in contrast to the studies of Alarcon et al [3] and D’Olhaberriague et al [15], where chorea and hemichorea-hemiballismus were reported as the most common acute movement disorders respectively. Hemiataxia was described as ataxic hemiparesis, hypesthetic hemiataxia, hypesthetic ataxic hemiparesis or sensory hemiataxia [14, 41, 42, 46, 47, 50, 51, 54, 55, 58, 63]. Dobato et al [14] reported 5 patients with sensory ataxic hemiparesis following thalamic haemorrhage, where all patients had loss of deep sensations like joint and position sense.…”
Section: Discussionmentioning
confidence: 99%
“…Fisher described isolated hemiataxia as a lacunar syndrome following lacunar in farction in the thalamus [3]. In a recent series of 17 patients with hemiataxia follow ing thalamic infarction, hemiataxia never occurred in isolation but was associated with ipsilateral sensory or motor disturbances, or both [4]. We also described a case of ataxic hemiparcsis following infarction restricted to the thalamus [5].…”
mentioning
confidence: 89%
“…MRI, 5 days later, revealed that it involved the pulvinar and ccntromedian, ventroposterolateral and ventral lateral nuclei. Since the observation of the 'syndrome ccrcbcllo-thalamiquc reported by Garcin [2] in 1955, incoordination of the cerebellar type in movement control resulting from thalamic lesions has often been debated [3]. Cerebellar ataxia due to thalamic involvement is never isolated but associated with corticospinal signs defining ataxic hemiparesis or both corticospinal signs and sensory' disturbances (painful or hypesthesia) defining hypesthesic ataxic hemiparesis.…”
Section: Casementioning
confidence: 99%
“…Cerebellar ataxia may be due to the interruption of the dentatorubrothalamocortical tract within the ventral lateral thalamic nucleus, which was the case for our patients. Sensory disturbances could have been caused by dam age to ascending spinothalamic or lcmniscal fibers within the ventro posterolateral nucleus [3]. These thalamic nuclei are supplied by the thalamogeniculate arteries [1].…”
Section: Casementioning
confidence: 99%